A Computational Model of Cognitive Maps: Analyzing Violent and Nonviolent Activity in Egypt and Germany. (March 2016) - Dornschneider, Stephanie; Henderson, Nick
Why do some individuals pick up arms as opposed to others who live under the same conditions? Environmental and group theories fail to differentiate between these individuals. In response, we apply the cognitive mapping approach and model violence as decisions based on chains of beliefs about various types of factors, including state aggression, access to violent groups, religion, and personal characteristics. Based on a double-paired comparison, data are constructed from ethnographic interviews with Muslim and non-Muslim individuals engaging in violent and nonviolent activity in authoritarian and democratic states—Egypt and Germany. The analysis develops a computational model formalizing the cognitive maps into Bayesian networks. In 477, 604 runs, the model (1) identifies the beliefs connected to decisions, (2) traces inference chains antecedent to decisions, and (3) explores counterfactuals. This suggests that both violent and nonviolent activities are responses to state aggression, and not to Islam, group access, or personal characteristics.